Anchovy Business Development Strategy: Islamic Economic Review (Case Study of Pasar Teradam Village, Barus District) - Nurbaiti Tanjung; Atika Atika; Nur Ahmadi Bi Rahmani (Institut Agama Islam Sunan Giri Ponorogo, 2026)
This study explores the development strategies of the anchovy business in Pasar Terandam Village, Barus District, Central Tapanuli Regency, from the perspective of Islamic economics. Although the business has great potential due to abundant marine resources and stable market demand, it still faces various challenges, such as limited capital, the absence of cooperatives, traditional processing technology, and the lack of application of Islamic economic principles. In addition, external factors such as climate change, market competition, and shifting consumer preferences pose further threats. This research employs a qualitative approach with SWOT analysis to identify strengths, weaknesses, opportunities, and threats, which are then integrated with Islamic economic values such as justice, solidarity, welfare, and sustainability. The findings indicate that relevant strategies include establishing Islamic cooperatives, improving access to Sharia-compliant financing, providing business management training based on Islamic values, innovating products and digital marketing, and applying fair profit distribution. These strategies are expected to support sustainable development of the anchovy business while enhancing the welfare of the local community.